L’overtourism come momento dell’attuale industria culturale - Distaso, Leonardo V. (Scenari, 2025)
A reflection on some aspects of mass tourism in regard to some of Adorno’s remarks on the subject of leisure and the reification of cultural heritage within the processes of the cultural industry. The bourgeois form of life that develops in the phase of late capitalism has transformed the tourist experience into an ideological confirmation of the forms of domination that mark the territories of culture along with the socio-economic ones. “The touristic man” becomes one more form of the contemporary consumer.